Faster turnover of taxonomic over functional bacterial composition during vermicomposting indicates increasing functional redundancy - Manuel Aira; Marcos Pérez-Losada; Keith A. Crandall; Jorge Domínguez (PLoS ONE, 2026)
Microbial taxonomy underpins microbial functionality; consequently, changes in taxonomic composition are expected to influence community functional profiles. However, functional redundancy—the ability of different microorganisms to perform similar functions—can sometimes decouple taxonomic and functional variation in microbial communities. In this study, we estimated the turnover rates of bacterial taxonomic and functional composition, as well as functional redundancy, across different substrates during vermicomposting. Our results showed that, during the early stages of vermicomposting, bacterial functional composition largely mirrored taxonomic composition across substrates. However, by the final stage, samples converged toward similar functional profiles despite remaining taxonomically distinct, indicating an increase in functional redundancy over time. Consistent with this pattern, the taxonomic turnover rate was approximately twelve times higher than the functional turnover rate. Functional redundancy increased throughout the process, with values ranging from 0.27 to 0.58 (on a scale from 0 to 1). The high turnover rates observed demonstrate that vermicomposting is an accelerated decomposition system with respect to both bacterial taxonomic and functional dynamics, exhibiting turnover rates more than 200 times higher than those reported for soil ecosystems. However, because this study did not include a non-earthworm control treatment, the accelerated turnover rates cannot be attributed exclusively to earthworm activity and should instead be interpreted as the result of the combined effects of earthworms and microorganisms. Future studies should incorporate non-worm controls to disentangle the specific contribution of earthworms and to evaluate how varying earthworm densities influence microbial turnover dynamics.